The influence of Brainstorming towards Students Writing Descriptive Text Ability at The Second Semester of The Seventh Class at SMP N 2 Bukit Kemuning Lampung Utara in 2014/2015 - Nurchurifiani, Eva (Lentera: Jurnal Ilmiah Kependidikan, 2016)
The problem of this research is many students get difficulties in writing especially in writing descriptive text. In this research the writer tried to investigateâ Brainstormingâ in teaching writing. The objectives of the research was to know and describe whether the average score of studentsâ ability in writing descriptive text which is taught through brainstorming is higher than which is taught through lecturing, to know and describe the influence of Brainstorming towards studentsâ ability in writing descriptive text. The research was conducted at the seventh class students of SMPN 2 Bukit Kemuning Lampung Utara in 2014/2015. In this research the writer used experimental method. The population of this research are 96 students. The writer took two classes as sample. The first class was VIIa as experiment class that consist of 32 students while VIIb as control class that consist of 32 students. The sample in this research was taken by using cluster random sampling technique. In data collecting technique, it was used written  test, it is include instruction that students should make a composition which consist at least 100 words based on the topics chosen, the topics are: My beloved mother, my best friend, my hometown. In data analysis, the writer used ttest formula. It was found that tratio > ttab. = 4.03 and ttable 2.00 So, the hypothesis null(Ho) is rejected and Hypothesis alternative (Ha) is accepted. It means that there is positive and significant influence of using Brainstorming towards studentsâ ability in writing descriptive text. Therefore to improve the studentsâ writing ability, the writer suggest that the teacher can use Brainstorming as an alternative technique in teaching writing and give more exercises in writing.